Analisis Leader Member Exchange, Budaya Organisasi Dan Komitmen Organisasi Terhadap Kinerja Manajerial - Asdani, Andi; Handayawati, Kuni Utami (Akutansi Bisnis & Manajemen ( ABM ), 2019)
Every organization (including those in tertiary institutions) who wish to persist in being a part of an increasingly competitive environment, must be supported by strong, powerful and high-performing human resources. This would include leaders who are able to direct their employees to achieve organizational goals. Therefore, management needs to pay great attention in realizing a strong organizational culture and applying the LMX theory in order to make the work atmosphere more pleasant and being able to use it as a "tool" in providing encouragement to employees in achieving an optimal performance. The purpose of this study was to determine the effect of leader member exchange (LMX) on organizational commitment, the effect of leader member exchange (LMX) on managerial performance, the effect of organizational culture on organizational commitment, the effect of organizational culture on managerial performance and the effect of organizational commitment on managerial performance. The population used in this study were employees at the Managerial Level in Malang State Polytechnic which constitutes each heads of divisions including the head of department and the head of study program at Malang State Polytechnic. Data was collected through distributing questionnaires that have been tested for its validity and reliability. Furthermore, A thorough analysis was conducted using the path analysis model. From the results of this study it was concluded that the LMX variable had a significant effect on managerial employee performance. This would mean that better performing employees would lead to better application of LMX. It was also founded that organizational culture had a significant effect on performance meaning that the better the application of organizational culture, the better the managerial performance. Henceforth, it can be determined that there is a direct influence of Leader Member Exchange (LMX) and Organizational Culture on Managerial Performance and there is an indirect influence on Leader Member Exchange (LMX) and Organizational Culture on managerial performance through organizational commitment